2004
DOI: 10.1080/0042098042000214770
|View full text |Cite
|
Sign up to set email alerts
|

From Land Use Right to Land Development Right: Institutional Change in China's Urban Development

Abstract: There has been a fundamental institutional change during the transformation from the centrally controlled system to a market-oriented economy in China since the early 1980s. The socialist land use right as an institution of the out-going central planning system became an obstacle to the emerging land market for urban redevelopment, although land leasing as a new institution had created a real estate market primarily for the development of greenfield sites. From a case study of a district in Shanghai, it is dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(93 citation statements)
references
References 20 publications
0
90
1
2
Order By: Relevance
“…This is contradictory with the findings of Qian [15] and He and others [24] who found that fiscal decentralization and political centralization have made local governments the leaders of land development. This finding is also contradictory to the study conducted by Zhu [51], focusing on the relationship of land use right and urban development in the early 1990s. The findings also suggest that the function of the market in recently developed cities like Nanjing is generally restricted by multiple urban plans.…”
Section: Relation Between Planned Areas and Urban Land Expansioncontrasting
confidence: 54%
“…This is contradictory with the findings of Qian [15] and He and others [24] who found that fiscal decentralization and political centralization have made local governments the leaders of land development. This finding is also contradictory to the study conducted by Zhu [51], focusing on the relationship of land use right and urban development in the early 1990s. The findings also suggest that the function of the market in recently developed cities like Nanjing is generally restricted by multiple urban plans.…”
Section: Relation Between Planned Areas and Urban Land Expansioncontrasting
confidence: 54%
“…As previous efforts to increase tenure security against the state such as the 1998 LML had proven largely ineffective to counter these trends. This was partly due to absence of a clear legal basis, limited awareness of applicable provisions, lack of a well-defined process for appeal, and the conflict of interest arising from the fact that in many cases local governments responsible for conversions are also the first instance for resolution of disputes, all of which meant that local leaders were often able to violate laws with relative impunity (Zhu 2004). For example, in 2001 only 12% of farmers were confident that their land will be protected against administrative readjustment (Schwarzwalder et al 2002).…”
Section: The Challenge Of Regulating Land Takingsmentioning
confidence: 99%
“…Government involvement is, however, high even for commercial developments almost half of which -45% overall and 65% in the central region-is initiated by higher levels of government, and only about one third by private investors. While the need for private investors to cede initiative to public servants has been noted as a possible source of higher transaction costs and opportunities for corruption (Zhu 2004, Cai et al 2005, our survey provides one of the first opportunities to test the validity of these claims on a broader basis.…”
Section: Aggregate Evidence On Land Takingsmentioning
confidence: 99%
“…Toprak merkezi planlama sistemince, kullanıcılara göre parsellere bölünmüştü. Kullanıcılar devlete bir işgal ücreti veya tazminat ödememekle birlikte kentlerdeki kullanıcılar "yeniden iskan" ücreti ödemekteydiler (Xie vd., 2002(Xie vd., : 1377Zhu, 2004Zhu, : 1251Walker ve Buck, 2007: 45). Arazi ıslahı ise ekonomik planlar çerçevesinde özel projelere dayalı olarak çalışma birimlerince yapılmaktaydı (Logan, 2002: 13).…”
Section: Kentsel Topraklarunclassified
“…Yükseklikleri ile yarışan gökdelenlerin egemen olduğu ve "Doğunun Manhattan"ı olarak adlandırılan (Li, 2003: 212) Şanghay'ın Pudong bölgesinde ise, 1988-2000 yılları arasında 10.224 ha toprak kiralanmıştır. Bu bölgede, 1993-2000 yılları arasında yeni inşaat için kullanılan toprak miktarı 26,3 milyon m2'dir (Zhu, 2004(Zhu, : 1252(Zhu, -1253. Başkent Pekin ise günümüzde çok katlı lüks konut inşaatı ile kuşatılmış durumdadır.…”
Section: Kentsel Topraklar: Kullanım Hakkının öZelleştirilmesiunclassified